Communicative practices among the Ashéninka of ponchoni of the Peruvian Amazon - Vílchez Jiménez, Elsa (2014)
We account on how some communicative forms are used by asheninka people, and how they are transmitted to the children living at Ponchoni village located in El Gran Pajonal zone. The arrangements are unique in the Amazon area because of their relationship with nature, the handling of myths and the discursive profile of the leader.